(untitled) (BIOM - Revue scientifique pour la biodiversité du Massif central, 2022)
The study of mollusks is not a discipline commonly practiced on a large part of the Massif central territory. My personal surveys started half a dozen years ago on a sector covering the basses Combrailles, the Cher valley, the Tronçais country, the western bourbonnais bocage, the Gouzon basin. This note is a synthesis of personnal field observations and gives some notions of abundance and evolution of various species.